30 Managing delivery in women with congenital heart disease: results from the cuban national programme for pregnancy and heart disease. (2nd February 2018) - Kinsella, C; Thorne, SA; Clift, PF; Hudsmith, LE; Bowater, S; Peraza, R Vasallo; Torga, JE Perez; Rubio, PA Roman
Abstract : Purpose: To provide an update on the delivery outcomes achieved in congenital heart disease (CHD) patients by the Cuban National Programme for Pregnancy and Heart Disease. Methods: This was a single-centre retrospective study on a prospectively collected database from 1 st January 2000 to 15th May 2017. Baseline data: demographics (age, province of origin), diagnosis, co-morbidities and functional status. Primary outcomes: duration of pregnancy, pregnancy outcome, any maternal or fetal complications. Results: Overall 467 pregnancies in 462 women reached the third trimester. Median age was 25 (21–29) years, with 71% of cases originating from Havana. Patients presented in NYHA class I (97%, n=453) or II (3%, n=14), 6% (n=27) of patients had arrhythmias, 1% (n=4) had significant co-morbidities, and 1% (n=4) had impaired left ventricular function. One pregnancy resulted in stillbirth, with the rest (n=466) resulting in live births (n=469) of median birth weight 3200 (2880–3420) grams. Median duration of gestation was 39 (38.6–40) weeks. Sixty-six percent (n=307) of patients had a vaginal delivery; caesarean section rates were 34% (n=161). Maternal cardiovascular complications (<0.5%, n=2), and obstetric complications (14%, n=67) did not result in mortality. Being small-for-gestational-age was the commonest complication (10%, n=48) in neonates, with zero mortality. Three neonates (1%) inherited congenital cardiac defects. Post-delivery NYHA functional status was class I in 84% (n=393) patients, class II in 16% (n=73) of patients and class III in one patient (<0.5%). Conclusion: Despite considerable resource constraints, in middle-income countries management of CHD pregnancies according to existing guidelines can achieve excellent outcomes.